Rb+ occlusion stabilized by vanadate in gastric H+/K+-ATPase at 25 ºC - Montes, Monica Raquel (2011)
Despite its similarity with the Na+/K+-ATPase, it has not been possible so far to isolate a K+-occluded state in the H+/K+-ATPase at room temperature. We report here results on the time course of formation of a state containing occluded Rb+ (as surrogate for K+) in H+/K+-ATPase from gastric vesicles at 25 °C. Alamethicin (a pore-forming peptide) showed to be a suitable agent to open vesicles, allowing a more efficient removal of Rb+ ions from the intravesicular medium than C12E8 (a non-ionic detergent). In the presence of vanadate and Mg2+, the time course of [86Rb]Rb+ uptake displayed a fast phase due to Rb+ occlusion. The specific inhibitor of the H+/K+-ATPase SCH28080 significantly reduces the amount of Rb+ occluded in the vanadate–H+/K+-ATPase complex. Occluded Rb+ varies with [Rb+] according to a hyperbolic function with K0.5 = 0.29 ± 0.06 mM. The complex between the Rb+-occluded state and vanadate proved to be very stable even after removal of free Mg2+ with EDTA. Our results yield a stoichiometry lower than one occluded Rb+ per phosphorylation site, which might be explained assuming that, unlike for the Na+/K+-ATPase, Mg2+-vanadate is unable to recruit all the Rb+-bound to the Rb+-occluded form of the Rb+–vanadate–H+/K+-ATPase complex.